Effectiveness the Laid-off Empowerment Program Case Study - Al-Rfou, Ahmad N (Journal of Asian Business Strategy, 2013)
The purpose of the study is to investigate the relationship between laid off personal characteristics and success Small and Medium-sized Businesses, (SMBs), which established by empowering laid off program in Jordan Cement Factories Company (JOCM), the study also trying to identify the main factors that contribute in success and failure SMBs for laid off. 73 questionnaires were analyzed to achieve the research objective. The results indicated that there was no significant difference in success SMBs for staff laid off based on age, education and experiences. 66% reported that their projects failed, 24% of respondents stated that their projects are unrealistic, and they aimed to get amount of money from the company, where they shut down the project after receiving the project grant.